Logical Thinking Improvement in Children Aged 5 to 6 Years Through Pop-Up Book - Hendi Dewantara; Ismaniar Ismaniar (Universitas Negeri Padang, 2021)
The study was set back by the children's low logic ability of 5-6 years age at nagari muaro, sijunjung district. One of the key factors that led to the alleged lack of interesting learning facilities /media. This study is aimed at seeing an increase in logical thinking ability in children as young as 5-6 years of age through the use of pop-up book media in the family at nagari muaro, sijunjung district. The type of research is quantitative using pseudo-experiment methods (quasi exsperiment) with pretest design and posttest. The research population is 15 people. While the sample of the six selected kids from jorong Pematang Sari Bulan, sampling retrieval techniques are used sampling samples. The data analysis USES t-test samples samples. As a result of the conclusion to the data collection and management, 1) before being given actions (pretests) the most logical thinking ability of children is seen but inconsistently, this is seen from tests given by researchers ata time when the pretesting of children is more questionable. 2) after being given a posttest of logical thinking ability, children are characterized at the most consistent level, as indicated by tests given by researchers during posttest sessions, children are more able to answer. 3) there is a sophisticated difference between pretest results and posttests after a child has used inside pop-up book media